The Kölner Fechtbuch: Context and Comparison - Farrell, Keith (Acta Periodica Duellatorum, 2021)
The Kölner Fechtbuch is a fascinating, unique treatise from the 16th century. Although it is tempting to compare it with the Liechtenauer tradition and to use knowledge, ideas and concepts from that tradition to interpret this book, this article shows that such an approach would be flawed. To demonstrate a proper examination and analysis of the longsword fighting system within the Kölner Fechtbuch , this article compares and contrasts it with 15th and 16th century sources with a connection to the Liechtenauer tradition, along with 16th century sources from other traditions. Furthermore, this article examines the Fechtschulen , their rules and their context, in an attempt to demonstrate that the Kölner Fechtbuch is an example of this style of fighting.